2014
DOI: 10.1016/j.ijrobp.2013.11.245
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional Magnetic Resonance Imaging Using Axial Body Area as Respiratory Surrogate: Initial Patient Results

Abstract: Purpose To evaluate the feasibility of a retrospective binning technique for 4-dimensional magnetic resonance imaging (4D-MRI) using body area (BA) as a respiratory surrogate. Methods and Materials Seven patients with hepatocellular carcinoma (4 of 7) or liver metastases (3 of 7) were enrolled in an institutional review board-approved prospective study. All patients were simulated with both computed tomography (CT) and MRI to acquire 3-dimensinal and 4D images for treatment planning. Multiple-slice multiple-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…The feasibility of this technique has been validated in our previous publication 9 , 10 and we will briefly describe this technique here.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The feasibility of this technique has been validated in our previous publication 9 , 10 and we will briefly describe this technique here.…”
Section: Methodsmentioning
confidence: 98%
“…Currently, we also developed a retrospective 4D‐MRI technique using body area (BA) as an internal respiratory surrogate (9) . Preliminary results in liver cancer patients have demonstrated the feasibility and fidelity of this technique (10) . However, unavoidable artifacts in the reconstructed 4D MR images were observed.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, we have previously demonstrated that a T2 * /T1-weighted retrospective 4D-MRI technique using a TrueFISP/FIESTA pulse sequence 15 can achieve adequate temporal resolution (∼3 frames/s), acceptable spatial resolution (1.8×1.8×5 mm), but suffered from suboptimal and inconsistent tumor contrast. In our preliminary patient study, we have observed large degree of intersubject variations in tumor contrast of the 4D-MRI (range: 4.57-45.00; standard deviation: 14.63), 16 presumably due to the admittedly suboptimal T2*/T1 weighting tumor contrast of TrueFISP/FIESTA. On the contrary, some MR sequences can provide better tumor contrast but are not fast enough for retrospective 4D-MRI.…”
Section: Introductionmentioning
confidence: 82%
“…The acquisition mode of that sequence is in sequential-mode. 25 Although cine-mode 4D-MRI is achieved by using TrueFISP/FIESTA sequences, 27,28 the same image intensity assignment is used in the cine-mode 4D-MRI XCAT simulation for image quality comparison purpose. The HASTE/SSFSE MRI image intensities were selected for both simulations also because it provided T2-weighted signals, which have a high tumor-to-tissue contrast.…”
Section: A Digital Phantom Simulation Studymentioning
confidence: 99%